Gestão de conteúdo na Embrapa - Enilda Alves Coelho (2006)
The rapid growth of information nowadays constitutes one of the great challenges in this information society. Outdated information, duplications, inconsistencies, low quality, among others, are frequent problems. In this scene, the information and knowledge management constitute a complex task for the organizations. So, the strategy of content management has been presented as a new way to face this challenge. It is pointed as the key of the modern information management. This work presents the main theoretical concepts related to enterprise content management. It is also, presented and argued, through a strategy of case study, a Web content management model applied to a Web site in a public organization, Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA). In summary, the Content Management is a complex process with interrelated activities that, in turn, are executed by distinct professionals in the organization. The information technologies constitute an important part of this process and are tools that help the users in a specific organizational context. The most effective content management process demands an ecological and integrated approach, based on social, organizational and technological components.